CASE REPORTSCoronary artery spontaneous dissection in a young male heavy smoker during bed rest - Arslan, Gokhan; Cingoz, Faruk; Bozlar, Ugur; Iyisoy, Atilla (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Spontaneous dissection of coronary artery (SDCA) is an extremely infrequent cause of acute cardiac ischaemic manifestations or sudden cardiac death with complex pathophysiology. This condition mostly affects young women in association with peripartum or postpartum status with no known risk factors for cardiovascular disease although some correlations have been noted with connective tissue disorders contraceptive use or intense physical activity. Herein, we report a case of spontaneous dissection of the left anterior descending artery during bed rest in a 24-year-old young man who had no risk factors except smoking or family history of coronary artery diseases.